Dune road - Green, Jane, 1968- (New York : Viking, 2009)
Set in the beach community of a tony Connecticut town, our heroine is a single mom who works for a famous--and famously reclusive--novelist. When she stumbles on a secret that the great man has kept hidden for years, she knows that there are plenty of women in town who would love to get their hands on it--including some who fancy the writer for themselves.
Keywords: Single mothers -- Fiction; Novelists -- Fiction; Secrecy -- Fiction; Connecticut -- Fiction